Overseas Indian citizen: a new `Setubandhan'? - Roy, Anupama (2006)
The provision for overseas citizenship along with other changes in citizenship rules introduced by the Indian government reveals a trend that reinforces cultural identity and principle of descent and blood ties as constitutive of Indian citizenship. While the provision for overseas Indian citizenship may offer an "opening up" of Indian citizenship through the introduction of extra-territoriality, it occludes a simultaneous "closing of ranks", with acquisition of citizenship through birth or by registration and naturalisation becoming more strengent. - Reproduced.
Keywords: Nationality - India; Nonresident Indians